An experimental study on listening comprehension problems, strategy use and strategy instruction in an Iranian context / Sara Nowrouzi - Nowrouzi, Sara (2014)
Since the late 1970s, listening has been recognized as an important skill in language learning due to its critical role in academic success, communication, comprehension of lectures, and it‘s positive influence ―on the development of other skills‖ and the overall language proficiency (Rizzi & Absalom, 2007; Dunkel, 1991a; Long, 1985; Krashen, 1996; Rost, 2002, cited in Vandergrift, 2007b, p. 191). Numerous studies have been conducted to help learners improve in this skill namely in the area of listening strategy research and problem identification (Murphy, 1985; Vandergrift, 1999; Ozeki, 2000; Goh, 2000; Cross, 2009). However, most of the strategy-related studies (Fujita, 1985; Bacon, 1992a; Paulauskas, 1994; Seo, 2000; Kohler, 2002; Carrier, 2003; Goh and Taib, 2006; Chen, 2007; Zeng, 2007) are not based on any prior identification of listening problems. Additionally, those studies that focus on problem identification (Goh, 2000; Hasan, 2000; Liu, 2002) are followed by strategy recommendations that have not been tested. The present study has aimed to examine more closely the EFL learners‘ self-perceived listening comprehension problems and strategy use before and after the listening strategy instruction phase to determine the effectiveness of the strategy instruction and the potential correlation among the perception of listening problems, strategy use, and listening comprehension. A mixed method design was employed. Data from the experimental and correlational study were the main sources and semi-structured interview was conducted to support the quantitative data. The participants were 70 Iranian tertiary level first-year EFL learners who were split into a control group and an experimental group. The data were collected through a Listening Comprehension Test (LCT), two questionnaires: one on Listening Comprehension Problems (LCPQ) and another on Listening Strategy Use (LSUQ), and semi-structured interview. Pre-and-post tests were administered on both groups but only the experimental group was interviewed after the treatment. The duration of the study was 12 weeks. The experimental group received listening strategy training but the control group was trained by traditional procedure (presentation, practice and production). The quantitative study results were significant but with differing effect sizes: compared to the control group, the experimental group perceived gains for all three components LCT, LCPQ and LSUQ but the effect size was large for the perception of listening strategy use (LSUQ) and small for the perception of listening comprehension problems (LCPQ) and the results of the listening comprehension tests (LCT). The correlational results revealed that the high level of listening strategy use do not necessarily lead to equally high level of success in listening comprehension or low level of listening problems. The qualitative results showed that after the treatment, the learners had problems in bottom-up processing listening skills and the strategies were only partly effective in solving these problems. Theoretically, the mixed method design of the study made explicit the quantitative and qualitative effect of strategy instruction on EFL learners‘ perceptions of their listening comprehension problems and strategy use; and pedagogically, the findings would be beneficial for those in the EFL context to be better informed in helping learners in using strategies more effectively.